TEACHING READING COMPREHENSION (AN OVERVIEW OF THE CONTENT-BASED SUMMARIZING) - Aratusa, Zana Chobita (Fakultas tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Palu, 2017)
Reading is an important skill for students, in particular for Islamic studies students who often study rich textual texts. They are required to understand and grasp information quickly form the texts. This requires teachers and students to poses approriate reading technique in a classroom teaching. Researchers have proposed many reading teaching techniques from traditional and modern perspectives in many reading classroom studies, but limited researchers have proposed an appropriate reading technique for summarizing a reading text in particular for Islamic studies students context. This paper proposes a content-based summarizing techniques for reading calssroom to improve students skill to grasp information faster compared to traditional techniques. The discussion of this paper shows that the content-based summrizing technique is potential to be implemented in a reading classroom, in particularly for Islamic studies classroom.